CD33 (Siglec-3) Inhibitory Function: Role in the NKG2D/DAP10 Activating Pathway - Trinidad Hernández-Caselles; Rubén Corral-San Miguel; Antonio José Ruiz-Alcaraz; Pilar García-Peñarrubia (Journal of Immunology Research)
CD33 (siglec-3), a well-known target in leukemia therapy, is an inhibitory sialoadhesin expressed in human leukocytes of the myeloid lineage and some lymphoid subsets, including NK cells. It may constitute a control mechanism of the innate immune system; nevertheless, its role as an inhibitory receptor remains elusive. Using human NK cells as a cellular model, we analyzed CD33 inhibitory function upon different activating receptors. In high-cytotoxicity NKL cells, CD33 displayed a prominent inhibition on cytotoxicity triggered by the activating receptors NKG2D and, in a lower extent, 2B4, whereas it did not inhibit NKp46-induced cytotoxicity. NKp46 was partially inhibited by CD33 only when low-cytotoxicity NKL cells were tested. CD33 triggering did not inhibit IFN-γ secretion, contrasting with ILT-2 and CD94/NKG2A inhibitory receptors that inhibited cytotoxicity and IFN-γ secretion induced by all activating receptors tested. CD33-mediated inhibition of NKG2D-induced triggering involved Vav1 dephosphorylation. Our results support the role of CD33 as an inhibitory receptor preferentially regulating the NKG2D/DAP10 cytotoxic signaling pathway, which could be involved in self-tolerance and tumor and infected cell recognition.